Domain-dependent effects of insulin and IGF-1 receptors on signalling and gene expression - Weikang Cai (Nature Portfolio, 2017)
Despite being structurally similar, the insulin receptor (IR) and insulin growth factor I receptor (IGF1R) elicit distinct signalling pathways. Here the authors use receptor chimeras to unveil that IR and IGF1R signalling is related primarily to differences in their intracellular juxtamembrane region.